Therapy service use among individuals with fragile X syndrome: findings from a US parent survey. (14th September 2012) - Martin, G. E.; Ausderau, K. K.; Raspa, M.; Bishop, E.; Mallya, U.; Bailey, D. B.
Abstract Background Fragile X syndrome (FXS) is known to be associated with a range of developmental challenges, yet the occurrence and intensity of therapy services along with associated factors have not been determined. Method In a US national survey, caregivers provided information regarding the therapy services received by their sons (n = 1013) and daughters (n = 283) with FXS (from birth to 63 years; mean = 15.6 years, SD = 10.6). Caregivers reported (1) type, (2) amount, (3) location, and (4) overall satisfaction with services. Associations with other child variables and family income were also examined. Results Key findings included that 72% of males and 47% of females were currently receiving at least one type of therapy service; the most common services for both males and females were speech–language therapy (ST) and occupational therapy (OT). Overall, males were more likely to receive therapy services as well as a greater number of services than females. Autism status was significantly associated with both males and females receiving ST and males receiving OT and behaviour management therapy. Therapies were provided in a variety of locations, and parents were generally satisfied with the amount and quality of therapy services. Age‐related declines were evident in the use of services for both males and females, with very few individuals receiving any therapy services after 20 years of age. Conclusions This study provides a baseline description of the current state of therapy services for children with FXS, laying a foundation for future research and recommendations for service provision and policy.